Penerapan Metode Proyek Dalam Meningkatkan Kemampuan Guru Dalam Pelaksanaan Pembelajaran - Kazwaini Kazwaini (STKIP ROKANIA, 2018)
The type of research is a school action research (PTS) that aims to know the success of the Application of Project Methods. To Improve Teacher's Ability in Creating Learning Media and Teacher's Ability in the implementation of learning at SDN. The population in this study was all teachers who are in the ability of teachers in the implementation of learning in the SDN located within the target area Researchers as school supervisors amounted to 13 people. From the description of data processing and discussion it can be concluded that the ability of teachers in the implementation of learning obtained in the first cycle of 63% with good category and in the second cycle increased to 78% with good category. This means that the implementation of the project method can improve the ability of teachers in the implementation of learning at SDN 015 Rokan IV Koto